2012
DOI: 10.1523/jneurosci.0877-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

A Widely Distributed Spectral Signature of Task-Negative Electrocorticography Responses Revealed during a Visuomotor Task in the Human Cortex

Abstract: While research of human cortical function has typically focused on task-related increases in neuronal activity, there is a growing interest in the complementary phenomenon-namely, task-induced reductions. Recent human BOLD fMRI studies have associated such reductions with a specific network termed the default mode network (DMN). However, detailed understanding of the spatiotemporal patterns of task-negative responses and particularly how they compare across different cortical networks is lacking. Here we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…For example, enhanced cognitive control following identification of response conflict is associated with increased gamma activity (as well as gamma-theta power-phase coupling) in LPFC [36]. Furthermore, in an intracranial EEG study, increased gamma power was observed during a visuomotor task in a range of frontal and posterior brain areas previously identified as being positively involved in this task [66]. In summary, localised gamma oscillations seem to promote the activation of task-relevant processes across the brain.…”
Section: Cortical Oscillations and Sustained Attentionmentioning
confidence: 90%
“…For example, enhanced cognitive control following identification of response conflict is associated with increased gamma activity (as well as gamma-theta power-phase coupling) in LPFC [36]. Furthermore, in an intracranial EEG study, increased gamma power was observed during a visuomotor task in a range of frontal and posterior brain areas previously identified as being positively involved in this task [66]. In summary, localised gamma oscillations seem to promote the activation of task-relevant processes across the brain.…”
Section: Cortical Oscillations and Sustained Attentionmentioning
confidence: 90%
“…One possible hypothesis is that spontaneous DMN activity is associated with both mind-wandering and stable behavior, each independently, because of separate neurophysiological processes. Increased BOLD activations are associated with local field potentials and broadband gamma-wave activity (37,38), whereas the basis of BOLD deactivations is complex and less well understood (39,40). Mind-wandering may be time-locked to DMN activation, as supported by findings indicating that autobiographical memory processes (typically engaged during mind-wandering) are associated with increased broadband gamma activity (41).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed a consistent finding related to DMN cortical deactivation during cognitive task performance is a transient suppression of the gamma band, which is time-locked to the onset of task performance and varies in amplitude in relation to task difficulty (21)(22)(23)(24). Conversely, gamma-band activity is elevated in human DMN structures during control conditions that include quiet wakefulness, fixating one's eyes on a target, or an eyes-closed condition.…”
Section: Significancementioning
confidence: 92%